Syntheses and Crystal Structure of Complex [Ni(5-iipa)(bbi)]n Based on 5-Iodoisophthalic Acid and 1, 1′-(1, 4-Butanediyl)bis(imidazole) Ligand. Issue 9 (1st September 2016) - Xu, Fu; Liu, Yu-Jie; Li, Fu-An
Abstract : A new polymer, [Ni(5-iipa)(bbi)] n (1 ) (5-iipa = 5-iodoisophthalic acid, bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole)), has been synthesized through hydrothermal reaction. It was structurally characterized by elemental analysis and X-ray single-crystal diffraction. The X-ray crystal structure shows that the complex belongs to orthorhombic system, P bca space group, and a = 10.1599(3) Å, b = 16.9413(2) Å, c = 22.1516(5) Å. The polymer exhibits an infinite [Ni2 (5-iipa)2 ] n double-chain, and such chains are further united together to generate a three-dimensional structure through bbi ligands. Adjacent 3D frameworks are interlaced each other in a parallel fashion to give rise to a twofold interpenetrating structure.